2018
DOI: 10.3892/br.2018.1064
|View full text |Cite
|
Sign up to set email alerts
|

Skin perfusion pressure as a predictor of ischemic wound healing potential (Review)

Abstract: Abstract. Skin perfusion pressure (SPP) is the blood pressure that is the requisite for the restoration of microcirculatory or capillary flow following controlled occlusion and subsequent flow return. The purpose of the current review was to evaluate the value of SPP for the prediction of wound healing in patients with limb ischemia. Articles published up to January 31, 2017 were searched in the PubMed database and Chinese database CNKI, using the keywords of 'skin perfusion pressure', 'limb ischemia' and 'wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
(60 reference statements)
1
11
0
Order By: Relevance
“…Such would indicate that SPP is an invaluable indicator of wound closure, irrespective of age or sex of the patient. Our results support similar trend findings on the utility and predictive potential of using SPP such as those reported in the meta-analysis conducted by Pan et al 14 …”
Section: Discussionsupporting
confidence: 93%
“…Such would indicate that SPP is an invaluable indicator of wound closure, irrespective of age or sex of the patient. Our results support similar trend findings on the utility and predictive potential of using SPP such as those reported in the meta-analysis conducted by Pan et al 14 …”
Section: Discussionsupporting
confidence: 93%
“…Among them, laser Doppler is fast, effective, and easy to operate and is the most widely used method of measuring SPP. 54 In a study by Yamamoto et al, the authors have found that an increase in SPP of 20 mm Hg after bypass surgery was associated with better limb prognosis. 55 Novel noninvasive techniques include the oxygen-to-see method, which is an optical measuring technique that combines white light spectrometry and laser Doppler flowmetry, mapping oxygen saturation, relative hemoglobin, and blood flow in target tissues.…”
Section: Risk Stratification Models and Time To Heal Predictors Aftermentioning
confidence: 98%
“…Among them, laser Doppler is fast, effective, and easy to operate and is the most widely used method of measuring SPP. 54 In a study by Yamamoto et al, the authors have found that an increase in SPP of ≥20 mm Hg after bypass surgery was associated with better limb prognosis. 55…”
Section: Introductionmentioning
confidence: 98%
“…In this way, SPP measurements calculate the capillary opening pressure and provide an indirect estimation of the microcirculatory flow status within the artery at skin level[ 34 ]. SPP is advantageous in that it is not altered by vascular calcifications[ 35 ]. Notably, SPP values > 30 mmHg after successful endovascular treatment with balloon angioplasty and/or stenting have been correlated with improved wound healing in a retrospective study of 113 consecutive CLI patients, with a sensitivity and a specificity of 81.4% and 69.2%, respectively[ 34 ].…”
Section: Laser Doppler Skin Perfusion Pressure Measurements and Transcutaneous Oxygen Monitoringmentioning
confidence: 99%
“…Similarly, in patients exhibiting abnormal involuntary movements, reliable measurements will also not be feasible[ 48 ]. Other factors such as site selection, electrode equilibration, patient age, patient positioning, patient status before examination, pain, smoking and caffeine consumption, skin temperature changes, sympathetic tone, tissue edema, hyperkeratosis, cellulitis, and local skin integrity[ 35 , 39 ] may affect the accuracy of measurements, hence decreasing overall reliability. In addition, bony prominences, larger veins, or varicose veins should be avoided during cuff placement for SPP measurements, since they may produce artifacts[ 48 ].…”
Section: Laser Doppler Skin Perfusion Pressure Measurements and Transcutaneous Oxygen Monitoringmentioning
confidence: 99%